Neologismer i norsk Kartlegging av leksikalsk språkendring før og nå - Fjeld, Ruth Vatvedt; Nygaard, Lars (Nordiske Studier i Leksikografi, 2010)
This article presents a short history of Norwegian neography and some of the problems in the field of lexical development, as well as attempts of classification of neologisms. It also presents a new, semiautomatic method of mapping neologisms from newspaper corpora. Some of the findings show that the overwhelming amount of new words in Norwegian are inherited words, mostly composite, and that loan words all in all are very few.